Impact of Semantic Relatedness on Associative Memory: An ERP Study - Desaunay, Pierre; Clochon, Patrice; Doidy, Franck; Lambrechts, Anna; Bowler, Dermot M.; Gérardin, Priscille; Baleyte, Jean-Marc; Eustache, Francis; Guillery-Girard, Bérengère (Frontiers in Human Neuroscience, 2017)
Encoding and retrieval processes in memory for pairs of pictures are thought to be influenced by inter-item similarity and by features of individual items. Using Event-Related Potentials, we aimed to identify how these processes impact on both the early mid-frontal FN400 and the Late Positive Component (LPC) potentials during associative retrieval of pictures. Twenty young adults undertook a sham task, using an incidental encoding of semantically related and unrelated pairs of drawings. At test, we conducted a recognition task in which participants were asked to identify target identical pairs of pictures, which could be semantically related or unrelated, among new and rearranged pairs. We observed semantic (related and unrelated pairs) and condition effects (old, rearranged, and new pairs) on the early mid-frontal potential. First, a lower amplitude was shown for identical and rearranged semantically related pairs, which might reflect a retrieval process driven by semantic cues. Second, among semantically unrelated pairs, we found a larger negativity for identical pairs, compared to rearranged and new ones, suggesting additional retrieval processing that focuses on associative information. We also observed an LPC old/new effect with a mid-parietal and a right occipito-parietal topography for semantically related and unrelated old pairs, demonstrating a recollection phenomenon irrespective of the degree of association. These findings suggest that associative recognition using visual stimuli begins at early stages of retrieval, and differs according to the degree of semantic relatedness among items. However, either strategy may ultimately lead to recollection processes.